3-Hydroxystearic acid promotes cholesterol efflux and attenuates atherosclerosis via the ALKBH5/PAX-8/ABCA1 pathway - Zhou, Qin-Yi; Liu, Wang; Zhao, Zhen-Wang; Gong, Duo; Ma, Xiao-Feng; Tang, Chao-Ke (Frontiers in Immunology, 2026)
IntroductionAtherosclerosis can trigger various cardiovascular and cerebrovascular diseases with complex pathogenesis. Macrophage proliferation, inflammatory responses, and lipid phagocytosis, which induce foam cell formation and accumulation, are critical in the development of early atherosclerotic lesions. The role of 3-Hydroxystearic acid (C18-3OH), a recently identified gut microbiota-derived metabolite, in atherosclerosis has not yet been clarified. This study aimed to investigate the role of the ALKBH5/PAX-8/ABCA1 pathway in C18-3OH-mediated regulation of macrophage cholesterol efflux and atherosclerosis and explore novel mechanisms of ABCA1 regulation from the perspective of m6A modification.MethodsRT-qPCR and Western blotting were used to detect gene and protein expression, respectively. ChIP-Seq was used to screen PAX-8 target genes, and ChIP-qPCR was used to validate PAX-8 binding to ABCA1. The SRAMP platform was used to predict m6A modification sites in PAX-8 mRNA sequences. Methylated RNA immunoprecipitation-qPCR (MeRIP-qPCR) was used to measure m6A modification levels of PAX-8 mRNA in foam cells. UHPLC-OEMS untargeted metabolomics were used to analyze differential fatty acid metabolites in an atherosclerotic mouse model. Specific kits were used to detect serum liver function markers (aspartate transaminase, AST; alanine aminotransferase, ALT), renal function markers (serum creatinine, Scr; blood urea nitrogen, BUN), and lipid profiles (HDL-C, TG, LDL-C, TC). Aortic sinus sections were prepared, and H&E, Oil Red O, and Masson staining were used to evaluate atherosclerotic plaques.ResultsThe results demonstrated that C18-3OH promoted cholesterol efflux in foam cells and alleviated lipid accumulation by upregulating ABCA1 expression. C18-3OH inhibited ALKBH5, increased PAX-8 mRNA m6A modification and PAX-8 expression, and upregulated ABCA1 to enhance cholesterol efflux. Serum metabolomics revealed reduced C18-3OH levels in high-fat diet-fed apoE-/- atherosclerotic mice. C18-3OH suppressed aortic ALKBH5 expression, elevated m6A modification of PAX-8 mRNA, and increased PAX-8 and ABCA1 expression. Furthermore, C18-3OH improved lipid metabolism and reduced the atherosclerotic plaque area in apoE-/- mice.DiscussionThis study clarifies the impact and mechanisms of gut microbiota-derived C18-3OH on atherosclerosis progression, providing novel strategies for the precise prevention and treatment of atherosclerosis.